Characterization of a basic phospholipase A2-homologue myotoxin isolated from the venom of the snake Bothrops neuwiedii (yarará chica) from Argentina - Geoghegan, Patricia (1999)
A basic protein was isolated by CM-Sephadex C-25 chromatography from the venom of Bothrops neuwiedii from Argentina, and named B. neuwiedii myotoxin I. This protein exerted local myotoxic and edema-forming e ects in mice, with potencies comparable to other myotoxins isolated from Bothrops spp. venoms. When injected by i.v. route at doses up to 4.7 mg/kg of body weight, the toxin was not lethal. In vitro, the toxin had no detectable phospholipase A2 activity on egg yolk phospholipids. B. neuwiedii myotoxin I appeared as a homodimer in sodium dodecylsulphate±polyacrylamide gel electrophoresis, with a subunit molecular weight of 15 kD. Gel immunodi usion revealed a pattern of partial antigenic identity between the newly isolated myotoxin and myotoxin II from Bothrops asper venom. The sequence of B. neuwiedii myotoxin I was determined for the ®rst 40 amino acid residues, showing high homology to several class II phospholipase A2 myotoxins of the Lys-49 family from crotalids. Altogether, results suggest that this toxin is a new member of the Lys-49 phospholipase A2-homologues with myotoxic, cytolytic, and edema-inducing activities